The Effectiveness of Implementation Telenursing in Health Education Intervention in Children With DM: Literature Review - Gita Apriani Br Tarigan (Jurnal KESANS : Kesehatan dan Sains, 2022)
Global technological advances occur in the development of health service information and communication systems, one of which is a nursing service information system. Telenursing is one of the information and communication system technologies for remote nursing services that is carried out virtually in providing nursing care practices. Based on data from the Indonesian Pediatrician Association (IDAI) that the incidence of DM has increased in children aged 0-18 years over a period of 10 years. However, in some countries that diabetic patients do not receive health education in conducting self-monitoring and control of complications. Generate descriptions and ideas from the selection of several literature reviews on the application of a communication system for nursing services, namely telenursing to facilitate the provision of health education interventions for DM children. Analyze and select nursing journals related to telenursing and Health Education in DM children. On the results of the analysis and review of several selected journals, a conclusion is obtained that telenursing communication technology can improve and facilitate nursing care services, namely Health Education in DM children. Nurses can use technology to improve nursing care services in conducting health education interventions that are easily accessible quickly and affordable by the community.